2020
DOI: 10.3390/medicina56080373
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography-Based Response to Target and Immunotherapies in Oncology

Abstract: 2-deoxy-2-[18F]fluoro-D-glucose ([18F]FDG) is a promising tool to support the evaluation of response to either target therapies or immunotherapy with immune checkpoint inhibitors both in clinical trials and, in selected patients, at the single patient’s level. The present review aims to discuss available evidence related to the use of [18F]FDG PET (Positron Emission Tomography) to evaluate the response to target therapies and immune checkpoint inhibitors. Criteria proposed for the standardization of the defini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 90 publications
(139 reference statements)
0
6
0
Order By: Relevance
“…Inflammatory infiltration and related tumor changes can also hamper the FDG PET/CTbased response's reliability. However, several studies have to date suggested a potential added value of this approach, at least in selected patients [24]. In a previous study by our group comparing the first response assessment to Nivolumab using CT and FDG PETbased criteria in the same cohort of patients, FDG imaging maintained a prognostic value even in patients classified as PD based on CT [28].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Inflammatory infiltration and related tumor changes can also hamper the FDG PET/CTbased response's reliability. However, several studies have to date suggested a potential added value of this approach, at least in selected patients [24]. In a previous study by our group comparing the first response assessment to Nivolumab using CT and FDG PETbased criteria in the same cohort of patients, FDG imaging maintained a prognostic value even in patients classified as PD based on CT [28].…”
Section: Discussionmentioning
confidence: 90%
“…As the anticancer immune response results from the complex interplay between T cells and other immune cells, peripheral biomarkers increased attention even in the setting of immunotherapy [19][20][21][22]. On the other hand, 18F-fluorodeoxyglucose positron emission tomography (FDG PET/CT) can display the tumor microenvironment's glucose consumption [23][24][25]. Thus, it is reasonable to assume that the combination of FDG PET/CT with systemic inflammation indexes might further improve cancer patients' prognostic stratification.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with morphologic imaging, [18F]FDG PET/CT images can early detect irAEs due to the increased uptake of [18F]FDG at these sites. This potentially allows for a rapid intervention in life-threatening cases, such as severe colitis, pneumonitis, and pancreatitis [ 127 , 151 ].…”
Section: In Vivo Biomarkers For Immunotherapy: Molecular Imagingmentioning
confidence: 99%
“…Finally, the emerging role of immunotherapy and in particular of immune checkpoints inhibitors (ICPIs) in several cancers, including HNC have further stimulated the development of PET-based prognostic biomarkers ( 66 ). RT can modify the expression of some receptor (as PD1/PD-L1) on cancer cells or on myeloid cells, which may affect response to PD-1-based immunotherapy.…”
Section: Role Of Molecular Imaging In Researchmentioning
confidence: 99%